2020
DOI: 10.1161/jaha.119.014324
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Ethyl Glucuronide as Measure of Alcohol Consumption and Risk of Cardiovascular Disease: A Population‐Based Cohort Study

Abstract: Background Moderate alcohol consumption has been associated with a lower risk of cardiovascular disease (CVD) and all‐cause mortality compared with heavy drinkers and abstainers. To date, studies have relied on self‐reported consumption, which may be prone to misclassification. Urinary ethyl glucuronide (EtG) is an alcohol metabolite and validated biomarker for recent alcohol consumption. We aimed to examine and compare the associations of self‐reported alcohol consumption and EtG with CVD and all‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…There were 87 studies identified by Stockwell et al 8 After inclusion of 20 new studies meeting inclusion criteria, there were a total of 107 cohort studies (eTable 1 in Supplement 1). [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Three coders (J. Z., F. A., and J. C.) reviewed all eligible studies to extract and code data independently from all studies fulfilling the inclusion criteria.…”
Section: By Includingmentioning
confidence: 99%
“…There were 87 studies identified by Stockwell et al 8 After inclusion of 20 new studies meeting inclusion criteria, there were a total of 107 cohort studies (eTable 1 in Supplement 1). [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Three coders (J. Z., F. A., and J. C.) reviewed all eligible studies to extract and code data independently from all studies fulfilling the inclusion criteria.…”
Section: By Includingmentioning
confidence: 99%
“…In support of this, the logistic regression analysis here revealed between group differences in the frequency of detection of both potential dietary biomarkers and medications. For example, S-allylcysteine, a biomarker for garlic consumption (35, 36) was enriched in the intervention group whilst ethyl glucuronide, a validated urine biomarker for alcohol consumption (37, 38) was depleted. The logistic regression also suggests an apparent depletion of imidazole proprionate.…”
Section: Discussionmentioning
confidence: 99%
“…The %CDT was calculated as the percentage of total transferrin concentrations. The reference values for %CDT ranged from 1.19% to 2.47% (1st-99th percentile) [31]. In comparison, values for %CDT have been reported to range from 1.01 to 2.85% in healthy subjects with an upper reference limit of 2.35% (97.5th percentile) using the N latex CDT direct immunonephelometric assay for serum CDT [30].…”
Section: Assessment Of Exposures and Other Risk Markersmentioning
confidence: 97%